National Cultural Differences in French-Finnish Alliances, - Focus on the Integration Phase - Räty, Marjaana (My University, 2003)
The purpose of the study was to look at how national cultural differences manifest themselves in French-Finnish alliances, and especially in the integration phase of the alliance life cycle. The objective was also to find out how applicable the dimensions of national culture are to the alliance context. Additionally also the future cultural challenges in French-Finnish alliances were aimed to be identified as well as the cultural training needs. In the literature review alliances and national culture were comprehensively treated. Also the previous studies of the impact of culture in cross-cultural alliances were identified, and the previous studies done in the French-Finnish context explored. As an outcome of the literature review, five main activities of the alliance integration phase were identified as: strategic orientation of the alliance, decision-making, reporting relationships, alliance governance and contract negotiations. 17 research propositions were formed by connecting the integration phase activities to national cultural dimensions. The cultural dimensions adopted in the study were power distance, uncertainty avoidance and individualism from Hofstede (1991), universalism from Trompenaars (1993), and monochronic/polychronic time from Hall (1976). The method of the study was a survey conducted with e-mail based questionnaires. The analysis included both quantitative and qualitative elements. The results were presented descriptively with frequency tables. The justifications given by the respondents to their answers were content analysed. Only seven propositions out of the 17 were supported. Cultural differences were noticeable in each main activity, yet the least in contract negotiations. From the cultural dimensions power distance and differences in time perception were most apparent. Uncertainty avoidance and particularism were less perceivable than in the previous studies. As a result, it was concluded that an international alliance is a fairly controlled environment, thus may diminish the impact of national cultural differences.
Keywords: national culture; alliance; alliance life cycle; France; Finland; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|